Digital Fundraising Model of Cash Waqf - Rahmatullah Rahmatullah; Bintang Ramadhan Putra (Jurnal Ilmiah Ekonomi Islam, 2020)
The purpose of this study is to offer a solution for waqf organizations that want to make digitally available waqf funds in a number of stages that need attention. The method used in this study is descriptive analysis by referring to a variety of reading sources. The results of this study are offered new levels of digital funding with digital analytic, digital vision, digital channel, digital campaign and digital report